Distribution of malignant neoplasms of the oral cavity in Ecuador: an epidemiological study from 2015 to 2019 - Karina Lalangui; Emmanuelle Quentin; Juan Marcos Parise-Vasco; Claudia Reytor-Gonzalez; Evelyn Frías-Toral; Daniel Simancas-Racines (Medwave)
Introduction Malignant neoplasms of the oral cavity represent a public health problem worldwide with an increasing incidence, especially in young populations. In Ecuador, the epidemiology of these conditions has been little studied, limiting timely diagnosis and management. The study aims to identify the distribution of hospitalizations and deaths from oral cavity malignant neoplasms in Ecuador during the pre-pandemic years, from 2015 to 2019, describing spatiotemporal patterns by province, gender, and age.